Considerations to Optimize Strength and Muscle Mass Gains Through Flywheel Resistance Devices: A Narrative Review. Issue 1 (28th February 2023) - Raya-González, Javier; Castillo, Daniel; de Keijzer, Kevin L.; Beato, Marco
ABSTRACT: Flywheel (FW) resistance training is a valid and time-efficient method to improve force production and muscular hypertrophy. However, no definitive consensus exists regarding FW parameters for optimizing chronic training responses. Therefore, this review aims to examine the FW training literature and provide evidence-based conclusions and practical applications for practitioners. This review reports that FW resistance training is a valid strategy to improve force, power, and hypertrophy responses; however, differences with traditional training programs have not been clearly established. It is not possible to state that FW training is superior to traditional resistance training methodologies. Moreover, the differences between populations and sex should be studied in further depth to establish robust conclusions. Finally, this review reports variables (duration, volume, and intensity) that should be adopted to improve force, power, and hypertrophy responses—even though future research is needed to establish the appropriate training dose for specific populations.